Designer Cranioplasty at Budget Prices: A Novel Use of 3D Printing Technology - Yerragunta, Thirumal; Kanala, Reddy Ramanadha; Yerramneni, Vamsi Krishna; Kolpakawar, Swapnil; Rangan, Vasundhara (Indian Journal of Neurosurgery, 2021)
Background Cranioplasty using synthetic materials for restoration of the exact shape of the skull has always remained a challenge until the development of 3D printing technology. However, the high-cost of available 3D printed implants limits their extensive use.Objectives To study the effectiveness of a low-cost, 3D-printed template for molding the polymethyl methacrylate (PMMA) (bone cement) in order to achieve exact contours of the skull specific to each patient.Materials and Methods 10 cranioplasties have been performed between July 2018 to December 2019 in a variety of craniotomy defects using bone cement flaps shaped using custom-made molds. The mold was 3D-printed and based on each patient’s CT images in digital imaging and communications in medicine (DICOM). Miniplates and screws were used to fix the flap. Postoperatively, clinical and radiological evaluation were done to assess patient satisfaction and accuracy of contour achieved.Results Patient satisfaction as well as accuracy of contouring, as seen on postoperative CT scans, were excellent. There were no notable complications on follow-up.Conclusion PMMA cranioplasty flap, contoured using a 3D-printed mold, is a very cost-effective alternative for restoration of skull contour for various craniotomy defects.Polymethyl methacrylate (PMMA) molded to form the exact shape of lost calvarium using 3D printed plastic templates is a smart and economical solution.
Keywords: Cranioplasty; PMMA (polymethylmethacrylate); 3D-printed, low-cost